Thin Air Resulting in High Pressure: Mountain Sickness and Hypoxia-Induced Pulmonary Hypertension - Jan Grimminger; Manuel Richter; Khodr Tello; Natascha Sommer; Henning Gall; Hossein Ardeschir Ghofrani (Canadian Respiratory Journal)
With rising altitude the partial pressure of oxygen falls. This phenomenon leads to hypobaric hypoxia at high altitude. Since more than 140 million people permanently live at heights above 2500 m and more than 35 million travel to these heights each year, understanding the mechanisms resulting in acute or chronic maladaptation of the human body to these circumstances is crucial. This review summarizes current knowledge of the body’s acute response to these circumstances, possible complications and their treatment, and health care issues resulting from long-term exposure to high altitude. It furthermore describes the characteristic mechanisms of adaptation to life in hypobaric hypoxia expressed by the three major ethnic groups permanently dwelling at high altitude. We additionally summarize current knowledge regarding possible treatment options for hypoxia-induced pulmonary hypertension by reviewing in vitro, rodent, and human studies in this area of research.